Gut Microbiota, Immunity, and Disease: A Complex Relationship - Kosiewicz, Michele M.; Zirnheld, Arin L.; Alard, Pascale (Frontiers in Microbiology, 2011)
Our immune system has evolved to recognize and eradicate pathogenic microbes. However, we have a symbiotic relationship with multiple species of bacteria that occupy the gut and comprise the natural commensal flora or microbiota. The microbiota is critically important for the breakdown of nutrients, and also assists in preventing colonization by potentially pathogenic bacteria. In addition, the gut commensal bacteria appear to be critical for the development of an optimally functioning immune system. Various studies have shown that individual species of the microbiota can induce very different types of immune cells (e.g., Th17 cells, Foxp3+ regulatory T cells) and responses, suggesting that the composition of the microbiota can have an important influence on the immune response. Although the microbiota resides in the gut, it appears to have a significant impact on the systemic immune response. Indeed, specific gut commensal bacteria have been shown to affect disease development in organs other than the gut, and depending on the species, have been found to have a wide range of effects on diseases from induction and exacerbation to inhibition and protection. In this review, we will focus on the role that the gut microbiota plays in the development and progression of inflammatory/autoimmune disease, and we will also touch upon its role in allergy and cancer.